1994
DOI: 10.1128/iai.62.5.1989-1994.1994
|View full text |Cite
|
Sign up to set email alerts
|

Proteus mirabilis fimbriae: identification, isolation, and characterization of a new ambient-temperature fimbria

Abstract: Urinary tract infections involving Proteus mirabilis may lead to complications including bladder and kidney stones, acute pyelonephritis, and bacteremia. This bacterium produces a number of fimbriae, two of which, MR/P fimbria and P. mirabilis fimbria, have been shown to contribute to the ability of this pathogen to colonize the bladder and kidney. We have now purified and characterized a previously undescribed fimbria of P. mirabilis, named ambient-temperature fimbria (ATF). Electron microscopy of a pure prep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(36 citation statements)
references
References 20 publications
1
35
0
Order By: Relevance
“…Both MR/P fimbriae and UCA/NAF were also found to vary in expression within a swarming colony of P. mirabilis (Latta et al, 1999). The ATF are preferentially expressed during static culture at 23°C in rich medium, but not culture at 42°C in minimal medium, or when grown on solid medium (Massad et al, 1994b). Mannose-resistant/ Klebsiella-like (MR/K) fimbriae, which are likely PMF , are known to be produced during static culture (Adegbola et al, 1983); however, because MR/K fimbriae were only characterized by erythrocyte binding (i.e.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Both MR/P fimbriae and UCA/NAF were also found to vary in expression within a swarming colony of P. mirabilis (Latta et al, 1999). The ATF are preferentially expressed during static culture at 23°C in rich medium, but not culture at 42°C in minimal medium, or when grown on solid medium (Massad et al, 1994b). Mannose-resistant/ Klebsiella-like (MR/K) fimbriae, which are likely PMF , are known to be produced during static culture (Adegbola et al, 1983); however, because MR/K fimbriae were only characterized by erythrocyte binding (i.e.…”
Section: Discussionmentioning
confidence: 94%
“…The remaining 12 potential fimbriae encoded by P. mirabilis (Pearson et al, 2008) remain uncharacterized. Multiple types of fimbriae can be expressed simultaneously (Adegbola et al, 1983;Massad et al, 1994b;Tolson et al, 1995). It is intriguing to consider whether MrpJ or its paralogues may contribute to regulation of fimbrial expression in addition to regulation of flagella, particularly in light of the different fimbrial appearances exhibited by mrpJ or ucaJ overexpression strains (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, we showed that yad is more strongly expressed at 308C and temperatures below that. Temperature is an important regulatory condition known to modulate multiple virulence factors, as well as other bacterial fimbriae which expression are higher at lower temperatures sometimes through the action of the H-NS silencing protein (Massad et al, 1994). In addition to H-NS temperature-dependent regulation, thermosensing mechanisms can act at different levels.…”
Section: Discussionmentioning
confidence: 99%
“…Mannose-resistant Proteus-like ¢mbriae (MR/P) and Proteus mirabilis ¢mbriae (PMF) have been proposed as important for virulence in UTI caused by P. mirabilis [3,10]. Ambient temperature ¢mbriae (ATF) were so named as their optimal expression temperature is 23³C (ambient temperature) [11]. The nucleotide sequence of the atf gene cluster revealed three genes: atfA, encoding a structural subunit (AtfA), atfB, encoding a chaperone (AtfB), and atfC, encoding a molecular usher (AtfC) [12].…”
Section: Introductionmentioning
confidence: 99%